PENGEMBANGAN MEDIA FLASH CARD PADA ELEMEN PENGERITINGAN DASAR DI SMK PAB 12 SAENTIS - Panjaitan, Deswita Sururi; Wahidah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the limited availability of learning media for the basic hair curling element, making it necessary to develop technology-based learning media that can systematically visualize work procedures at SMK PAB 12 Saentis. Therefore, this study aimed to develop an Flash Card learning media and determine its feasibility for the basic hair curling element at SMK PAB 12 Saentis. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The product was validated by material experts and media experts. The product trials were conducted in three stages: a small-group trial involving 5 students, a medium-group trial involving 10 students, and a large-group trial involving 31 students. Data were collected using Likert-scale questionnaires and analyzed using descriptive analysis. The results showed that the Flash Card learning media was categorized as highly feasible for use in learning the basic hair curling element. The material expert validation obtained an average score of 90.47%, while the media expert validation obtained an average score of 90.22%. The product trial results achieved 86% in the small-group trial, 90% in the medium-group trial, and 95.03% in the large-group trial, with an overall average of 92.95%, which falls into the Highly Feasible category. Therefore, the Flash Card learning media is considered highly feasible for use as a learning medium in the basic hair curling element at SMK PAB 12 Saentis.